REGIONAL REVENUES, AUDIT OPINIONS, LOCAL GOVERNMENT FINANCIAL PERFORMANCE: THE MODERATING ROLE OF CAPITAL EXPENDITURE - Eva Yunadia Chaerani; Amrie Firmansyah (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
The existence of regional autonomy policies causes regional governments to have their respective authorities in administering government. It encourages increased performance and accountability. In addition, the Covid-19 outbreak that has hit has made people increasingly pay attention to the performance of local governments. This research examines the factors influencing the financial performance of local governments in districts/cities in South Sulawesi. The independent variables used are regional revenue and audit opinion. This study also aims to investigate the effect of capital expenditure as a moderator in the connection between the independent and dependent variables. This study employs secondary data from www.djpk.kemenkeu.go.id and https://e-ppid.bpk.go.id/, as well as multiple linear regression analytic approaches. This research finds that regional revenue significantly negatively affects local government financial performance. In addition, audit opinions significantly positively influence financial performance. However, capital expenditure does not have a moderating role in these two relationships.